Analysis of the 2D:4D ratios of national and amateur football players - Acar, H.; Tutkun, E. (International Journal of Applied Exercise Physiology, 2019)
2D:4D has been identified as a biomarker for performance in various elite sports. The aim of the study is to analyze the relationship between league status and 2D:4D ratios of national and amateur football players. 38 football players participated to this study who deserved participation FCBEscola Antalya and Istanbul camps according to the scouting results. 19 of players were national football players who have taken place at least one time in U14 and U15 Turkish national football teams and 19 of them were amateur players. The height, body weight, body mass index and 2D:4D finger measurements of the participants were taken. For the differences in the measurements results of the groups, the independent t-test was carried out and the results were evaluated in the p?0.05 significance level. In both groups a statistically significant difference was found between the right and left hand 2D:4D average values (p<0.05), and the right hand 2D:4D ratios were found to be lower than the left hand 2D:4D ratios. When compared the 2D:4D ratios of national and amateur players, it was determined that there was a statistically significant difference were found between the right hand 2D:4D ratios (p<0.05). Both right and left hand 2D:4D averages in national football players were found to be lower than the amateur football players. As a result of this study, it can be said that 2D:4D may discriminate between national and amateur footballers, and lower 2D:4D ratios could be linked to performance for football players. But for the healthier evaluation of the relationship between sportive performance and 2D:4D ratios, other determinative talent identification parameters should be taken together.